2008
DOI: 10.1002/anie.200704146
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium Iodide as the Precursor to the Control Agent in Ab Initio Emulsion Polymerization

Abstract: Iodide does the job: Water‐soluble, harmless, cheap, and nonhazardous NaI was used in combination with K2S2O8 instead of I2 itself to produce an uncolored living poly(butyl acrylate) latex of controlled molecular weight by a single‐step polymerization process (see scheme for one polymerization pathway). Reactivation of the polymer then yielded a block‐copolymer latex. BuA=butyl acrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…Equally important, the I 2 (or a precursor such as NaI 11,12 ) is low cost when compared with thiocarbonyl derivatives, organometallic complexes, or nitroxide derivatives. Moreover, controlled polymerization of styrene and (meth)acrylic monomers has been carried out successfully by RITP in homogeneous 8,9,13 and heterogeneous 14,15 systems demonstrating the versatility of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Equally important, the I 2 (or a precursor such as NaI 11,12 ) is low cost when compared with thiocarbonyl derivatives, organometallic complexes, or nitroxide derivatives. Moreover, controlled polymerization of styrene and (meth)acrylic monomers has been carried out successfully by RITP in homogeneous 8,9,13 and heterogeneous 14,15 systems demonstrating the versatility of the process.…”
Section: Introductionmentioning
confidence: 99%
“…This again would indicate that the lithium iodide catalysed cyclisation does not involve the direct oxidation via elemental iodine. Iodide may reduce a peroxide intermediate from arial oxidation of the diamine precursor 12 or there may be a role for small amounts of iodine to mediate in the radical oxidation as has recently been described for the additionfragmentation chain transfer processes in living radical polymer synthesis [26].…”
Section: Scheme 5 Iodine Catalysed Oxidation and Rearrangement Of Exo2mentioning
confidence: 98%
“…The Hawkett group is a pioneer of emulsion RAFT. 51 In these ways, the control agent concentrations were one order greater than the theoretical concentration (<0.3 mM) for synthesis of ultra-high MW PS. 44 Charleux et al reported on emulsion RAFT with a wide range of water-soluble control agents.…”
Section: Bulk Terp Of Styrenementioning
confidence: 99%